Programa preuniversitario de líneas de tiempo en el mejoramiento de aprendizajes en ciencias sociales en estudiantes de quinto grado de secundaria en la Institución Educativa Colegio Nacional Iquitos San Juan Bautista 2021 - Yahuana Pasapera, Roder (2023)
The main objective of this study was to assess the effect of a learner-training program based on timelines to improve fifth year students’ learning achievements in social sciences at Colegio Nacional Iquitos secondary school 2021. The study is evaluative in type with designs of field study, transactional contemporary, univariate, and quasi-experimental. The main data gathering tool was a valid and reliable performance test. Results show that the experimental group outperformed the control group as their mean score was higher (13.750 > 8.798), with most students of the experimental group (60.7%) being at “in process” achievement followed by 35.7% at “expected” level of achievement, whilst most students of the control group (76.9%) being at “beginning” level. The same happens in its dimensions: Construction of historic interpretations (12.917 > 8.141), responsible management of space and environment (15.071 > 11.769), and responsible management of economic resources (13.429 > 6.615). In conclusion, the learner-training program based on timelines improves significantly the population students’ performance in social sciences as p-value in the U test of Mann-Whitney was 0,000 < α = 0,05 in the variable and its dimensions.